(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The notion of reactive power management encompasses a wide range of system and customer challenges, particularly those connected to power quality, because most power quality issues may be mitigated or remedied with proper reactive power control. When strong inductive loads are coupled to transmission lines, the trailing load current causes a problem with power factor. In some cases, very low current flows through the transmission line due to minor load, resulting in a leading parasitic capacitance in the line, resulting experience extreme, causing the load side hand voltage must become twice that of the sending end side voltage (Ferranti effect), especially in long transmission system. To avoid this problem, we developed a new hybrid reactive power control model that uses a simultaneous combo of thyristor controlled reactor (TCR) and thyristor switched capacitor (TSC), which will immediately include a sleek current control spectrum from touch sensitive to deductive approach values by varying the firing angle of the transformer via a computer.